2023
DOI: 10.1111/jgh.16125
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of machine learning models and nomogram for the prediction of severe acute pancreatitis

Abstract: Background and Aim Severe acute pancreatitis (SAP) in patients progresses rapidly and can cause multiple organ failures associated with high mortality. We aimed to train a machine learning (ML) model and establish a nomogram that could identify SAP, early in the course of acute pancreatitis (AP). Methods In this retrospective study, 631 patients with AP were enrolled in the training cohort. For predicting SAP early, five supervised ML models were employed, such as random forest (RF), K‐nearest neighbors (KNN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These newly identified studies were screened based on the inclusion and exclusion criteria. Finally, a total of 33 original studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were included. The literature screening process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These newly identified studies were screened based on the inclusion and exclusion criteria. Finally, a total of 33 original studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were included. The literature screening process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were conducted in 8 countries, including 1 [ 30 ] in Germany, 1 [ 26 ] in Hungary, 1 [ 17 ] in South Korea, 1 [ 37 ] in Nepal, 1 [ 18 ] in Sweden, 2 [ 20 , 21 ] in UK, 3 [ 22 , 28 , 43 ] in the USA, with the remaining studies conducted in China. Ten [ 23 , 24 , 26 , 27 , 30 , 31 , 34 , 35 , 40 , 41 ] studies were multicenter studies, while two studies [ 18 , 20 ] collected subjects from databases. Eleven studies [ [14] , [15] , [16] , 18 , [20] , [21] , [22] , 25 , 26 , 31 , 35 ] considered overfitting, and k-fold cross-validation was primarily used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective analysis involving 648 AP patients, Hong et al [ 158 ] developed RF and logistic regression models using a training sample; the RF model, notable for its interpretability, showcased the most superior discriminative performance in predicting SAP. In a retrospective study involving 631 AP patients, Luo et al [ 159 ] developed a machine learning model, culminating in a nomogram designed for the early identification of SAP during the progression of AP. Their findings indicated that the RF model delivered optimal predictive performance, with the nomogram offering a visual scoring model suitable for clinical application[ 159 ].…”
Section: Aimentioning
confidence: 99%
“…In a retrospective study involving 631 AP patients, Luo et al [ 159 ] developed a machine learning model, culminating in a nomogram designed for the early identification of SAP during the progression of AP. Their findings indicated that the RF model delivered optimal predictive performance, with the nomogram offering a visual scoring model suitable for clinical application[ 159 ]. Such models have the potential to act as functional tools, enabling personalized treatment choices and enhancing clinical results by stratifying AP patients prior to treatment[ 159 ].…”
Section: Aimentioning
confidence: 99%